Endothelial retargeting of AAV9 in vivo. (3rd October 2022) - Bozoglu, T; Lee, S; Ziegler, T; Kupatt, C
Abstract: Background: Adeno-associated virus (AAV) is favorable choice for gene transfer and gene editing applications in vivo, due to its low integration rate and low immunogenicity, as well as a variety of natural and engineered serotypes providing different tissue and cell type tropism. Endothelial cells, however, are remarkably resistant to transduction by AAVs. Purpose: The aim of this study is to retarget wild type AAV9 vectors using a combination of polyamidoamine dendrimers (PAMAM) and peptides with endothelial affinity. Methods: An endothelial-affine peptide sequence was obtained via bio-panning of a phage display library on endothelial culture cells. Second-generation PAMAM dendrimers were linked to the peptide via PEG linker. AAV9 vectors were coated with these modified dendrimers (G2CNN) immediately before in vivo applications. Results: mTmG-mice or mTmG-pigs were utilized as reporter organisms, where red-to green fluorescence change upon Cre expression displays cellular resolution of transduction. Cre encoding AAV coated with G2CNN application systemically (mice) or locally (pigs) transduced over 30% of CD31+ cells in skeletal muscle and heart. Functional relevance of endothelial retargeting was assessed by systemic injections of G2CNN coated AAV9 encoding for three transgenes: 1) An artificial adhesion molecule (S1FG). In wild type mice, S1FG expression in endothelial cells increased leukocyte adhesion in cremaster muscle vasculature (day 10 post injection). 2) Anti-inflammatory Annexin A1 (Anxa1). In ApoE−/− mice on high-fat diet, Anxa1 expression reduced long term leukocyte recruitment in carotid artery (day 28 post injection). 3) sgRNA targeting the vasodilatory enzyme eNOS (endothelial nitric oxide synthase). In conditional Cas9 transgenic mice, editing of eNOS via AAV delivered Cre and sgRNA caused increase of blood pressure (day 56 post injection). Conclusion: Endothelial retargeted AAV9 efficiently transduced endothelial cells of skeletal muscle and heart in vivo. Accordingly, in vascular and atherosclerosis models, these modified vectors may enable gene transfer. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Bundesministerium für Bildung und ForschungDeutsche Forschungsgemeinschaft